Quranic letter pronunciation analysis based on spectrogram technique: case study on Qalqalah letters - Altalmas, Tareq; Ahmad, Salmiah; Sediono, Wahju; Hassan, Surul Shahbudin (2015)
Recitation of the Holy Quran with Tajweed is an essential activity as a Muslim. Reciting Quran correctly indicates the correct meaning of the words of Allah has been received from this significant resource among Muslims. That is why Muslims stress on the Quranic Education since in the early age. It is important to pronounce the letter correctly based on its characteristics as well as the articulation point of each letter. In this paper, the characteristic based on Qalqalah letters is considered to be analyzed. The audio signal from a person who is very good at Quranic recitation was taken and analyzed. We implement spectral analysis to find the features of Qalqalah letters and extract the correlation between the first formant frequency and the pharyngeal space of the signal. Spectrogram was successfully implemented and proved this relation, and it described the mechanism of Qalqalah correctly, which is unique as compared to other Quranic letters.